Neuroprotective effects of fingolimod in mouse models of Parkinson's disease. Issue 1 (26th September 2016) - Zhao, Peng; Yang, Xiaoxia; Yang, Liu; Li, Minshu; Wood, Kristofer; Liu, Qiang; Zhu, Xiaodong
Abstract : Parkinson's disease (PD) is characterized by a progressive loss of dopaminergic neurons with limited treatment options. Emerging evidence shows that FTY720 protects against neural injury via modulation of the sphingosine‐1‐phosphate 1 receptor (S1PR1). However, it remains unclear whether FTY720 could influence neurodegeneration in PD. Therefore, the present study was designed to determine the impact of fingolimod (FTY720), a sphingosine‐1‐phosphate receptor (S1PR) agonist, on 2 mouse models of PD. We found that FTY720 significantly reduced the deficit of motor function, diminished the loss of tyrosine hydroxylase–positive neurons in the substantia nigra, and attenuated the decrease of striatal dopamine and metabolite levels in mice receiving 6‐hydroxydopamine (6‐OHDA) or rotenone to simulate PD. An S1PR1‐selective antagonist, W146, blocked the neuroprotective effects of FTY720. Of note, FTY720 retained the phosphorylation of ERK, together with a decreased expression of cleaved caspase‐3 inmice treated with 6‐OHDA or rotenone. In vitro studies revealed that FTY720 also attenuated 6‐OHDA‐ or rotenone‐induced toxicity in SH‐SY5Y cells. These findings suggest the potential of S1PR modulation as a treatment for PD.—Zhao, P., Yang, X., Yang, L., Li, M., Wood, K., Liu, Q., Zhu, X. Neuroprotective effects of fingolimod in mouse models of Parkinson's disease. FASEB J. 31, 172–179 (2017) www.fasebj.org